The Effects of Sarcopenia and Fracture Risk on Kinesiophobia, Fear of Falling, Fall Risk and Quality of Life in Geriatric Individuals - Hilal Telli; Çağla Özdemir (Galenos Yayinevi, 2024)
Objective: This study aimed to determine the relationship between sarcopenia and fracture risk in older adults and to investigate the effects of increased fracture risk in individuals with sarcopenia on the fear of falling, fall risk, kinesiophobia, and quality of life (QOL). Materials and Methods: The study involved 132 participants. Sarcopenia risk was assessed using the SARC-F questionnaire, fracture risk with the Fracture Risk Assessment Tool, QOL with the "World Health Organization Quality of Life Scale" short form, presence of kinesiophobia with the TAMPA Kinesiophobia scale, and fall risk with the "Berg Balance scale" and "International Fall Effectiveness scale". Results: The study included 102 women (77.3%) and 30 men (23.7%). The average age of the individuals was 70.83±6.98. There was a risk of sarcopenia in 55.5% of patients, and those at risk of sarcopenia had a 33.3% risk of hip fracture and 22.2% risk of both hip and major fracture. With regard to the risk of sarcopenia, it was observed that the fall and fracture risks increased, and the QOL decreased (p-value <0.05). Fracture risk and sarcopenia risk were higher in women, increased with age, and negatively correlated with body mass index and education level (p-value <0.05). It has been observed that both fracture risk and sarcopenia risk with fracture risk increased the risk of falls, kinesiophobia, and decreased QOL (p-value <0.05). Conclusion: Appropriate treatment and early intervention of these conditions in sarcopenic individuals with isarcopenia and increased fracture risk may provide clinical benefits to reduce the risk of falls and fractures and improve QOL.